2020
DOI: 10.1093/rheumatology/keaa414
|View full text |Cite
|
Sign up to set email alerts
|

Association of systemic lupus erythematosus with peripheral arterial disease: a meta-analysis of literature studies

Abstract: Objective SLE patients have an increased cardiovascular morbidity and mortality. Contrasting data are available about the association between peripheral arterial disease (PAD) and SLE. We aimed to perform a meta-analysis of studies evaluating the association between SLE and PAD. Methods Studies were systematically searched in the PubMed, Web of Science, Scopus and EMBASE databases according to preferred reporting items for sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Our primary analysis identified ApoB as the major lipoprotein-related trait responsible for both PAD and CAD risk. This finding is consistent with a recent meta-analysis of 22 studies (including 1,892 PAD cases and 30,937 controls) which found significantly higher ApoB levels among PAD cases compared to controls (28). A nested case-control study within the Physicians’ Health Study (PHS) similarly identified baseline ApoB levels (in addition to several other lipid fractions) as a significant predictor of incident PAD (29).…”
Section: Discussionsupporting
confidence: 92%
“…Our primary analysis identified ApoB as the major lipoprotein-related trait responsible for both PAD and CAD risk. This finding is consistent with a recent meta-analysis of 22 studies (including 1,892 PAD cases and 30,937 controls) which found significantly higher ApoB levels among PAD cases compared to controls (28). A nested case-control study within the Physicians’ Health Study (PHS) similarly identified baseline ApoB levels (in addition to several other lipid fractions) as a significant predictor of incident PAD (29).…”
Section: Discussionsupporting
confidence: 92%
“…Peripheral arterial disease is often asymptomatic, and the ankle-brachial index (ABI) is typically used to assess for subclinical disease [51]. The prevalence of PAD in SLE has been reported between 21 and 33% [52][53][54]. SLE patients are four times more likely to have PAD (OR 3.9, 95% CI 1.8-7.9), compared with controls [54].…”
Section: Peripheral Arterial Diseasementioning
confidence: 99%
“…The prevalence of PAD in SLE has been reported between 21 and 33% [52][53][54]. SLE patients are four times more likely to have PAD (OR 3.9, 95% CI 1.8-7.9), compared with controls [54]. A retrospective review of the Taiwan National Health Insurance program data identified a ninefold higher risk of PAD (HR 9.39, 95% CI 7.70-11.5) in SLE patients, compared with controls [32].…”
Section: Peripheral Arterial Diseasementioning
confidence: 99%
“…SLE is a systemic autoimmune disease, characterized by the presence of a wide variety of autoantibodies and multiple organ system involvement [40]. SLE is characterized by a plethora of clinical manifestations, leading to fatal complications and chronic disability requiring tailored rehabilitation strategies [41][42][43][44][45]. Thrombosis substantially contributes to morbidity and mortality in this clinical setting, being related to a complex interaction between traditional thrombotic risk factors, systemic inflammation, and autoimmunity [40].…”
Section: Apl Ppositivity and Systemic Lupus Erythematosusmentioning
confidence: 99%